Changes of Cholesterol and Triglyceride in Human Serum After the Aerobic Activity - POURVAGHAR, M.J. (Asian Journal of Chemistry, 2010)
Some specialists supposed that cholesterol and triglyceride could play an effective role in creating cardiovascular diseases. But, in spite of the numerous researches in the field, the question of whether or not triglyceride can lead to cardiovascular disease is still there. Instead, cholesterol has been recognized as a deleterious factor. Medical research findings indicate that there is a strong relationship between too much cholesterol in the blood or cholesterol serum and the possibility of heart coronary disease. In the present study, 15 male physical education students with average age of 24.2 ± 2.17 and average weight of 64.93 ± 5.12 kg and the average height of 171.6 ± 5.69 cm voluntarily participated in this quasi-experimental research. They were then formally invited to take part in the experiment by the specialists. Given the fact that the observed triglyceride (2.560) was found to be smaller than the critical triglyceride (2.997), it can be concluded that an aerobic activity (a single-session, 20 min jog) leads to no meaningful changes in the blood cholesterol rate. After activity, the blood serum cholesterol rate of athletics had increased 3.74 % in comparison with the blood serum cholesterol rate before activity. Furthermore, observed triglyceride (0.95) was smaller than critical triglyceride (2.997). It can be concluded that an aerobic activity leads to no meaningful changes in the blood triglyceride rate. After activity, their blood serum triglyceride rate had increased (3.44%) in comparison with the blood serum cholesterol rate before activity. There was no the acceptable correlation between their relative weight and their triglyceride and cholersterol rate. The obtained correlation (Pearson coefficient of correlation) computed at cholesterol rate and their relative weight in fasting conditions was (0.403) and also triglyceride and their relative weight (0.491). It can be concluded that there is an average correlation between measured factors and their relative weight.